Employee Participation and Collective Bargaining in Europe and China - Basedow, Jürgen; Chen Su; Matteo Fornasier; Liukkunen, Ulla (Mohr Siebeck, 2023)
Collective labour law is, for the most part, national law. It is often the result of social struggle and political compromise occurring in the national context. Unlike other fields of private law, it has not been the object of legal harmonisation, at either international or European levels. However, as national frontiers progressively open up for goods and services, collective labour law has become increasingly exposed to international and supranational law. This book contains the papers presented at an international conference held at the Max Planck Institute for Comparative and International Private Law in 2014. The authors look, from a comparative perspective, at current developments in the fields of collective bargaining and employee participation in several European countries and in China. They analyse the extent to which differences between the national legal systems still prevail and whether common features are about to emerge.